2021
DOI: 10.3390/cells10102618
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids Activate NLRP3 Inflammasome, Promoting Murine Liver Inflammation or Fibrosis in a Cell Type-Specific Manner

Abstract: Bile acids (BA) as important signaling molecules are considered crucial in development of cholestatic liver injury, but there is limited understanding on the involved cell types and signaling pathways. The aim of this study was to evaluate the inflammatory and fibrotic potential of key BA and the role of distinct liver cell subsets focusing on the NLRP3 inflammasome. C57BL/6 wild-type (WT) and Nlrp3−/− mice were fed with a diet supplemented with cholic (CA), deoxycholic (DCA) or lithocholic acid (LCA) for 7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…24 Holtmann et al found distinct bile acid induced NLRP3 inflammasome activates of HSCs, promoting fibrosis or inflammation. 46 By comparison, LCA feeding led to the most severe liver damage and activation of the NLRP3 inflammasome. The tracing studies have shown that liver damage and HSC activation were ameliorated in NLRP3 deficient cells or mice.…”
Section: Papermentioning
confidence: 99%
“…24 Holtmann et al found distinct bile acid induced NLRP3 inflammasome activates of HSCs, promoting fibrosis or inflammation. 46 By comparison, LCA feeding led to the most severe liver damage and activation of the NLRP3 inflammasome. The tracing studies have shown that liver damage and HSC activation were ameliorated in NLRP3 deficient cells or mice.…”
Section: Papermentioning
confidence: 99%
“…Liver fibrosis was promoted by DCA feeding, with an upregulation in NLRP3 in primary hepatic stellate cells. These signals, however, were decreased in Nlrp3−/− mice or cells [ 576 ].…”
Section: Intestinal Barrier Features In Nafldmentioning
confidence: 99%
“…Elevated levels of BAs induce the production of pro-inflammatory mediators in hepatocytes, attracting immune cells and initiating inflammation in the liver, eventually leading to cholestatic liver damage [ 15 ]. Furthermore, besides direct cytotoxic liver damage from BAs, oxidative stress and BA-induced mitochondrial damage lead to an inflammatory cascade [ 13 , 16 ]. The NLR family pyrin domain containing 3 (NLRP3) inflammasome in hepatic stellate cells and Kupffer cells is activated by BAs, causing inflammation or fibrosis [ 16 ].…”
Section: Pathophysiology Etiology and Complications Of Icpmentioning
confidence: 99%
“…Furthermore, besides direct cytotoxic liver damage from BAs, oxidative stress and BA-induced mitochondrial damage lead to an inflammatory cascade [ 13 , 16 ]. The NLR family pyrin domain containing 3 (NLRP3) inflammasome in hepatic stellate cells and Kupffer cells is activated by BAs, causing inflammation or fibrosis [ 16 ]. The level of intracellular γ-glutamyl-L-cysteinyl-glycine (GSH), which protects cells against oxidative stress, cell proliferation, and division, is significantly influenced by inflammation and oxidative stress related to cholestasis [ 17 ].…”
Section: Pathophysiology Etiology and Complications Of Icpmentioning
confidence: 99%